2017
DOI: 10.1136/bmj.j1710
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients for intra-arterial treatment for acute ischaemic stroke: development and validation of a clinical decision tool in two randomised trials

Abstract: Objective To improve the selection of patients with acute ischaemic stroke for intra-arterial treatment using a clinical decision tool to predict individual treatment benefit. Design Multivariable regression modelling with data from two randomised controlled clinical trials. Setting 16 hospitals in the Netherlands (derivation cohort) and 58 hospitals in the United States, Canada, Australia, and Europe (validation cohort). Participants 500 patients from the Multicenter Randomised Clinical Trial of Endovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 44 publications
6
121
1
Order By: Relevance
“…With regards to radiological predictors, baseline CT ASPECTS was a significant predictor of outcome in univariate analysis, as demonstrated before [8, 9, 12-14, 17, 29]. However, in multivariate analysis, CT ASPECTS was not an independent predictor of outcome.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…With regards to radiological predictors, baseline CT ASPECTS was a significant predictor of outcome in univariate analysis, as demonstrated before [8, 9, 12-14, 17, 29]. However, in multivariate analysis, CT ASPECTS was not an independent predictor of outcome.…”
Section: Discussionsupporting
confidence: 57%
“…Some studies found that collateral status was not an independent predictor of outcome when other variables were taken into account [14, 38]. Our results suggest that CT/CTA findings at presentation are of limited value for predicting clinical outcome and should be interpreted with caution [8, 42]. …”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations